Toxigenic fungi associated with stored, fruits of chironji - and MADHULIKA NIGAM, NEETA SHARMA, RATNA GHOSH (NAYEK) (Indian Phytopathology, 2002)
Samples of chironji (Buchanania lanzan) were collected on a random basis from different storage systems (stored for 4-9 months) from various shops in Lucknow, Uttar Pradesh, India, during December 1996 to June 1997. The fungi associated with the stored fruit were investigated by the blotter and agar plate methods. The most frequently isolated fungi were Alternaria alternata, Aspergillus flavus, A. ochraceus, A. niger, A. aculeatus, A. funiculosus, Cladosporium sp., Chaetomium globosum, Curvularia lunata [Cochliobolus lunatus], Fusarium moniliforme [Gibberella fujikuroi], Fusarium semitectum [Fusarium pallidoroseum], Macrophomina phaseolina, Mucor varians, Penicillium citrinum, Trichothecium roseum, Rhizopus arrhizus and Verticillium. A. flavus had the highest incidence (90%) and the incidence of the other fungi ranged from 2-30%. Ninety different samples were screened for mycotoxins; 4 mycotoxigenic fungi, A. flavus, A. ochraceus, G. fujikuroi and P. citrinum, the main producers of aflatoxin, ochratoxin, zearalenone and citrinin, respectively, were of common occurrence in the stored fruits of chironji.